Female catfight in Mark Waters' Mean Girls (2004) (Cinematology: Journal Anthology of Film and Television Studies, 2025)
Mean Girls (2004), an America drama movie directed by Mark Waters, demonstrates how female catfights in popular culture are often problematically portrayed as ‘normal’ and humorous, while simultaneously reinforcing sexist and patriarchal ideologies. The film portrays women who compete for social status and male attention. Consequently, it sustains negative stereotypes about female relationships The objective of this research is to identify and analyze how female catfighting is represented in Mean Girls. Employing qualitative approach within a pop culture studies, this analysis applies Stuart Hall’s concept of representation, Rachel Reinke’s concept of female catfighting, and Angela McRobbie’s post-feminist masquerade. Mulvey’s concept of male gaze is also utilized to dismantle how dominant ideology presents women through visuals. The data consist of narrative, dialogue, and visual elements from Mean Girls. The research findings posit that the movie represents female catfight through the characters Cady Heron and Regina George, who are constructed within a patriarchal framework. Additionally, the film also highlights the male gaze and how female identity is linked to physical appearance. Although the ending of the movie offers a slight sense of resistance at the end, overall, it still reflects the ideological values of a sexist popular culture.